Ekumenizm na drodze przemian: problemy i wyzwania - Tadeusz Kałużny (Polonia Sacra)
The author of the article has aimed at briefly outlining the present situation of the ecumenical movement. In the course of the reflection, he states that in the history of the ecumenical movement, the period of initial enthusiasm and dynamic development has given place to a period in which difficulties are experienced. Satisfaction with the doubtless achievements goes side by side with a sense of disappointment and discouragement resulting from the fact that the desired unity has not been possible to realize despite the efforts taken. However, this is not a time of stagnation or ice age, as some think, but, rather, time of approaching maturity, of estimating the way covered and recognizing new challenges. All this leads us to the conclusion that, at present, ecumenism is in a deepreaching process of transformation. It focuses especially on issues such as: 1) the aim of ecumenism, 2) the partners of dialogue, 3) ecumenical paradigm, 4) confessional identity, 5) reception of the achievements of dialogue. No doubt, the way to full unity is longer and harder than many have expected. However, the ecumenical involvement of the Roman Catholic Church is irreversible. The problems noted and the new challenges in the field of ecumenism should inspire one to a more intense and deep effort for the sake of bringing back full and visible union of all Christ’s disciples.